The Business of Big Data: How Data Collection Influences Consumer Behavior and Market Trends - Irfan Rashid (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
In the digital transformation era, the strategic use of big data is a key mechanism defining consumer behavior and influencing market trends. This study explores how businesses collect, analyze, and utilize consumer information to create personalized appeals, leverage marketing opportunities, and anticipate buying habits. Based on empirical research and industry reports, the paper highlights the symbiotic relationship between data-driven decision-making and consumer responses. Furthermore, it addresses critical ethical considerations, including privacy, transparency, and informed consent in data collection practices. Ultimately, these findings indicate that while big data offers businesses unparalleled foresight into future marketplace dynamics, it also necessitates responsible data management to maintain consumer trust and ensure sustainable market growth.